The Vacuolar H+ ATPase α3 Subunit Negatively Regulates Migration and Invasion of Human Pancreatic Ductal Adenocarcinoma Cells - Flinck, Mette; Hagelund, Sofie; Gorbatenko, Andrej; Severin, Marc; Pedraz-Cuesta, Elena; Novak, Ivana; Stock, Christian; Pedersen, Stine Falsig (Cells (Basel, Switzerland), 2020)
Increased metabolic acid production and upregulation of net acid extrusion render pH homeostasis profoundly dysregulated in many cancers. Plasma membrane activity of vacuolar H+ ATPases (V-ATPases) has been implicated in acid extrusion and invasiveness of some cancers, yet often on the basis of unspecific inhibitors. Serving as a membrane anchor directing V-ATPase localization, the a subunit of the V0 domain of the V-ATPase (ATP6V0a1-4) is particularly interesting in this regard. Here, we map the regulation and roles of ATP6V0a3 in migration, invasion, and growth in pancreatic ductal adenocarcinoma (PDAC) cells. a3 mRNA and protein levels were upregulated in PDAC cell lines compared to non-cancer pancreatic epithelial cells. Under control conditions, a3 localization was mainly endo-/lysosomal, and its knockdown had no detectable effect on pHi regulation after acid loading. V-ATPase inhibition, but not a3 knockdown, increased HIF-1α expression and decreased proliferation and autophagic flux under both starved and non-starved conditions, and spheroid growth of PDAC cells was also unaffected by a3 knockdown. Strikingly, a3 knockdown increased migration and transwell invasion of Panc-1 and BxPC-3 PDAC cells, and increased gelatin degradation in BxPC-3 cells yet decreased it in Panc-1 cells. We conclude that in these PDAC cells, a3 is upregulated and negatively regulates migration and invasion, likely in part via effects on extracellular matrix degradation.